Engineering the Biosynthesis of Caffeic Acid in Saccharomyces cerevisiae with Heterologous Enzyme Combinations. (April 2019) - Liu, Lanqing; Liu, Hong; Zhang, Wei; Yao, Mingdong; Li, Bingzhi; Liu, Duo; Yuan, Yingjin
Abstract: Engineering the biosynthesis of plant-derived natural products in microbes presents several challenges, especially when the expression and activation of the plant cytochrome P450 enzyme is required. By recruiting two enzymes—HpaB and HpaC—from several bacteria, we constructed functional 4-hydroxyphenylacetate 3-hydroxylase (4HPA3H) in Saccharomyces cerevisiae to take on a role similar to that of the plant-derived cytochrome P450 enzyme and produce caffeic acid. Along with a common tyrosine ammonia lyase (TAL), the different combinations of HpaB and HpaC presented varied capabilities in producing the target product, caffeic acid, from the substrate, L -tyrosine. The highest production of caffeic acid was obtained with the enzyme combination of HpaB from Pseudomonas aeruginosa and HpaC from Salmonella enterica, which yielded up to (289.4 ± 4.6) mg·L −1 in shake-flask cultivation. The compatibility of heterologous enzymes within a yeast chassis was effectively improved, as the caffeic acid production was increased by 40 times from the initial yield. Six key amino acid residues around the flavin adenine dinucleotide (FAD) binding domain in HpaB from Pseudomonas aeruginosa were differentiate from those other HpaBs, and might play critical roles in affecting enzyme activity. We have thus established an effective approach to construct a highly efficient yeast system to synthesize non-native hydroxylated phenylpropanoids.